Power Buck Converter Controlled by a Model Predictive Control to Integrate a Wind Energy Conversion System to a DC Micro grid - M. N. Suneetha, C. Lakshmi Narayana, (Design Engineering, 2021)
Renewable Energy Sources (RES) likewind, solar, biomass, tidaletc are quite popular. Suitable devices help in obtaining electric power from them. But energy output of these sources depends on the prevailing environmental conditions and the parameters of thegenerated power often vary. Thus the challenge lies in obtaining a constant output from a varying input.  The RES are integrated to electrical distribution systems through power electronic interface. Therefore power converters have attained a significant   role   in the present world. In thispaper,DC-DC power buck converter is utilised in integrating the output ofthe Wind Energy Conversion System(WECS) to DC Micro grid. Wind turbine mechanical output drives  three phase Self Excited Induction Generator(SEIG).  AC output power of SEIGcan be rectified and, supplies power to the buck converter, integrated to a 110V DC Micro grid. Due to varying wind conditions the torque output of the wind turbine varies and results in variation of input voltage to buck converter. To maintain output ofbuck converter at 110V under variable inputvoltage conditions,ModelPredictiveController(MPC) is used.Buck converter modelled in   average   state   space is used in designing MPC. The designed controller improves the performance of buck converter under both dynamic and steadystate conditions. The MPC does not affect the stability of the buck converter. The performance of the MPC designed is analysed for varying input   and   the performance is   compared with Proportional Integral Derivative(PID) controller. MATLAB is used for the simulations.